Роль диференціації знань лідерства та інструменти їх оцінки - Zaverbnyj, Andrij; Redina, Yevheniia; Matseliukh, Yurii (Dr. Viktor Koval, 2019)
Introduction. The development of liberal forms of management is accompanied by a rapid increase in the number of leaders. Therefore, the selection among the number of ordinary individuals is exactly those that meet the criteria of the leader, is an important problem. The most relevant in the situation of permanent elections is the search for such approaches to the differentiation of the role of leader, which would contribute to the development of society and the formation of those values that have deep civilizational influences. This led to the need for research and analysis of the role differentiation of leadership abilities that from ordinary people turn them into prominent personalities that change the present. Aim and tasks. The aim of the study is to study the existing experience of highlighting the qualities of leaders among a number of personality abilities, to study the approaches to their evaluation, use of acquired knowledge to assess the role differentiation of leadership abilities of senior and middle managers of IT market companies, testing the proposed approach to the example and unification of the proposed approach for assessing the role differentiation of leadership abilities of the first hundred richest people in the world. Results. The article analyzes foreign and domestic experience of highlighting the qualities of leaders among a number of personality abilities. Among the investigated approaches to assessing leadership qualities, an expert method for determining weight ratios was chosen that is best suited for companies in the gaming industry and digital distribution, to which Valve Corporation belongs. The results of the role differentiation of leadership qualities showed that in the figure of the most important are professional abilities, a little less have features related to interaction with subordinates, and the least - personal attributes. The petal diagram indicates a shift to professional abilities that plays a key role in the IT business. The proposed approach to the role-based differentiation of leadership abilities in the context of organizational changes in IT market companies can also be used in assessing the leadership abilities of the first hundred richest people in the world. Conclusions. The article examines foreign and domestic experience of highlighting the qualities of leaders among a number of personality abilities. The study of approaches to assessing leadership qualities and the possibilities of their use for companies in the field of gaming industry and digital distribution, which belongs to Valve Corporation. The offered approach of role differentiation of leadership abilities can be used both in the assessment of leadership abilities of the first hundred richest people in the world, and for the role differentiation of leadership abilities in the context of organizational changes in IT market companies.